THE IMPLEMENTATION OF MULTIMEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS - Agung Sulistiyono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2019)
This study was aimed to describe the implementation of multimedia in teaching English to young learners at SD Kristen Manahan Surakarta in the academic year 2016/ 2017 involving the teaching and learning activities, the learner’s role, the teacher’s role and the role of instructional materials. Besides that, the strength and weakness of using multimedia to teach English to young learners .were also described. It was a case study conducted at second to fifth grade students of SD Kristen Manahan, Surakarta and the teacher. This study was conducted in classes 2A, 2B, 2C, 3A, 3B, 3C, 4A, 4B, 4C, 5A and 5B.The investigation concerned in the implementation of multimedia in teaching English to young learners. The techniques of collecting the data were interview, observation and documentation. The data were analyzed by using descriptive qualitative method. The results showed that multimedia were used not only to teach English but also to assess the students’ achievement. The teacher facilitated the students’ needs, created and operated the multimedia, monitored the class activities, managed the class and became a partner for her students. The students, however, were passive in the implementation of multimedia. Concerning the strength and weakness of implementation of multimedia in teaching English to young learners at SD Kristen Manahan, the result showed five strong points. It helped students in understanding materials better, brought fun to the students, the interest of student was increased, it helped the teacher in preparing the teaching and learning process and cost of the materials was reduced. However, it had five weaknesses. It took time for preparing multimedia devices; not all the multimedia devices were ready to use; the boredom of students, electricity matters, the difficulties to find the proper source. Keywords: Implementation of Multimedia, Young Learners, Case Study, English Teaching.